Integrasi Media Audio-Visual dalam Song-Based Language Instruction pada pembelajaran Bahasa Ingggris bagi Siswa Sekolah Dasar - Irmawaty Umar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program was conducted at SDN 88 Kota Gorontalo to enhance young learners’ engagement and participation in English learning through the integration of audio-visual media within a song-based instructional approach. English instruction at the elementary level often faces challenges related to limited attention span, low motivation, and minimal exposure to authentic language input. To address these issues, this program implemented an instructional design combining songs with audio-visual support to create a more engaging and meaningful learning environment.The activity was carried out in three main stages: material presentation, structured practice, and interactive performative activities. Audio-visual media were utilized to provide contextualized language input, reinforce pronunciation, and stimulate students’ multimodal learning experiences. Songs were selected based on age appropriateness, linguistic simplicity, and thematic relevance to the topic of parts of the body.The results indicated increased student participation, improved pronunciation accuracy, and greater confidence in responding to English instructions. Students demonstrated higher enthusiasm and were more actively involved during singing and movement-based activities. The integration of visual and auditory stimuli helped learners better comprehend and retain vocabulary.This program implies that combining audio-visual media with song-based instruction can serve as an effective pedagogical strategy for young learners. The approach not only supports language acquisition but also fosters a positive and enjoyable classroom atmosphere in elementary English education.